PERSEPSI BANK MANDIRI CABANG PAHLAWAN SURABAYA TERHADAP SENAM AEROBIK - wulandari, dwi wulan; Sulistyarto, Soni (Jurnal Kesehatan Olahraga, 2019)
Abstract Perception is a process of compiling, recognizing, and interpreting sensory information that can be useful to provide an overview and understanding of the surrounding environment. The perceptions of each individual will vary, in bank employees who work under pressure and physical activity that is very lacking that can affect the body. Aerobic exercise can be done to make it a sport to improve the quality of work. The purpose of the study was to analyze and assess the perceptions of Surabaya branch independent bank employees on aerobic exercise. Type of quantitative descriptive research, research conducted to describe symptoms, phenomena or events. The results of the study obtained from 30 respondents indicated that the perceptions of employees were measured from the process indicators of receiving stimuli (good), moderate physiology / anatomy, background (good), experience (very good), attention (very good), movement (moderate), intensity, size, replication and something new said (good). Then it can be concluded that the perception of the independent bank branch of Surabaya hero on aerobic exercise is good which means that they are enthusiastic in doing aerobic exercise and have influence in their body and activities.   Keywords: Perception, Aerobic Gymnastics, quality of work.